Analisis Perbedaan Tingkat Kepatuhan Wajib Pajak Sebelum Dan Sesudah Penerapan E-Filing di Kota Padang - Annissa Deffira; Rahmat Kurniawan (Ekonomis: Journal of Economics and Business, 2021)
This study aims to test whether there are significant differences in the compliance of private taxpayers at the time before and after the implementation of e-filing?. Based on the hypothesis analyzed using paired t-test with the help of SPSS, in 100 samples tested, it can be concluded that there are significant differences in the compliance of private taxpayers, especially in SPT reporting before and after the application of e-filing. This can be proven from the test results paired t-test that shows the value of sig. (2-tailed) of 0.000 which is smaller than 0.05, as well as the average value of personal taxpayer compliance after the application of e-filing is 41.86 which is greater than the average value before the application of e-filing of 29.31 with an average difference of 12.55.